Beetle heads down south - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
It may be that only the sea at the Cape of Good Hope can halt the inexorable advance of the larger grain borer (LGB), Prostephanus truncatus, in southern Africa. Even that might not help, since it arrived from the Americas by boat, in a food relief...